Community Information Group as Village Public Relations Media: An Islamic Communication Approach in the Digital Age - Prismadani, Nindia Galuh; Noevi Rahmanto, Andre; Sudarmo (Sahafa Journal of Islamic Communication, 2024)
Abstrack This study aims to determine the role of the Community Information Community (KIM) as public relations at the village level which is oriented to disseminate accurate information through internal discussions first and has the aim that the community around the KIM area where researchers will discuss Biting Village, Ponorogo can actively participate. This is used so that the community can be empowered for their own village. KIM is formed independently by and for the community itself. KIM runs according to the corridor, namely to build social communication by continuing to strive for improvement and development within the internal institution. Then this can be seen from the official website of Biting Village, which began to be active in disseminating Biting Village activities to provide the latest news. The research method used is descriptive qualitative method through literature study, namely data collection from existing data sources such as data related to KIM. The methodology or approach used in this paper uses a library research method or approach, while data collection is carried out by reviewing and/or exploring several journals, books, and documents (both printed and electronic) as well as other sources of data and or information that are considered relevant to the study. The conclusion in this study is that KIM in Biting Village has an important role in becoming village public relations, namely a liaison between the government and the community, which makes it easier for communication between the two. So Biting Village KIM has carried out the role of village public relations well, because it has succeeded in empowering the community by participating in village development, one of which is the success in creating an official website owned by Biting Village KIM. Keywords: Community Information Group; Public Relations